The Poopó polymetallic epithermal deposit, Bolivia: Mineralogy, genetic constraints, and distribution of critical elements - Torres, B.; Melgarejo i Draper, J.C.; Torró, L.; Camprubí, A.; Castillo-Oliver, M.; Artiaga, D.; Campeny, M.; Tauler, E.; Jiménez–Franco, A.; Alfonso, P.; Arce-Burgoa, O.R. (MDPI, 2019)
The tin-rich polymetallic epithermal deposit of Poopó, of plausible Late Miocene age, is part of the Bolivian Tin Belt. As an epithermal low sulfidation mineralisation, it represents a typological end-member within the “family” of Bolivian tin deposits. The emplacement of the mineralisation was controlled by the regional fault zone that constitutes the geological border between the Bolivian Altiplano and the Eastern Andes Cordillera. In addition to Sn and Ag, its economic interest resides in its potential in critical elements as In, Ga and Ge. This paper provides the first systematic characterisation of the complex mineralogy and mineral chemistry of the Poopó deposit with the twofold aim of identifying the mineral carriers of critical elements and endeavouring to ascertain plausible metallogenic processes for the formation of this deposit, by means of a multi-methodological approach. The poor development of hydrothermal alteration assemblage, the abundance of sulphosalts and the replacement of löllingite and pyrrhotite by arsenopyrite and pyrite, respectively, indicate that this deposit is ascribed to the low-sulphidation subtype of epithermal deposits, with excursions into higher states of sulphidation. Additionally, the occurrence of pyrophyllite and topaz has been interpreted as the result of discrete pulses of high-sulphidation magmatic fluids. The δ34SVCDT range in sulphides (−5.9 to −2.8‰) is compatible either with: (i) hybrid sulphur sources (i.e., magmatic and sedimentary or metasedimentary); or (ii) a sole magmatic source involving magmas that derived from partial melting of sedimentary rocks or underwent crustal assimilation. In their overall contents in critical elements (In, Ga and Ge), the key minerals in the Poopó deposit, based on their abundance in the deposit and compositions, are rhodostannite, franckeite, cassiterite, stannite and, less importantly, teallite, sphalerite and jamesonite.
Keywords: Epithermal deposit; Critical elements; Bolivian Tin Belt; https://purl.org/pe-repo/ocde/ford#1.05.02